SELECTION OF THE BEST COFFEE SHOP USING THE VIKOR METHOD - Hutagalung, Juniar; Sari, Vina Winda; Aini, Zulfa (JURTEKSI (jurnal Teknologi dan Sistem Informasi), 2023)
Coffee businesses in Medan are becoming increasingly competitive. Due to the invention of coffee menus and coffee serving packaging to remain competitive, every coffee shop has a distinct quality. However, choosing the finest coffee shop remains a challenge for the decision-maker in this scenario, the consumer. Therefore, we need a mechanism to pick which clients or visits to a coffee shop. Clear, simple-to-understand idea-winning tactics make it simple to make decisions that are effective. The efficacy of various choices may be assessed by an efficient computer procedure. The purpose of this study is to use the Visekriterijumsko Kompromisno Rangiranje (Vikor) technique to choose the best coffee shop based on the following criteria: ambience, taste, pricing, diversity of the menu, service, and facilities. The responses of the questionnaire are used to determine the weight gain based on weighing. The option with the lowest value is chosen as the best option when A5 = 0. In other words, alternative A5 was chosen as the spot where coffee is most strongly recommended